Patrimonio, apuntes de gestión - García, Guillermo; Lapenta, Alicia; Luchetti, Jorge; Madia, Enrique H.; Noelle, Louise; Pataro, M. Susana (Grupo Habitat : Diseño, 2014)
A key contribution to support the Latin American community in the protection of their heritage and a current contribution of the views and experiences of region in the international forum.